Changes in the absolute configuration of the basal/flagellar apparatus and evidence of centrin during male gametogenesis in Chara contraria var. nitelloides (Charales, Charophyta) - Vouilloud, Amelia Alejandra Beatriz; Caceres, Eduardo Jorge; Leonardi, Patricia Ines (Plant Systematics and Evolution)
The absolute configurations of the basal/flagellar apparatus during male gametogenesis of Chara contraria var. nitelloides (Charales, Charophyta) were carefully analysed. Emphasis was placed on the changes in the angles and lengths of the basal bodies, the microtubular root angles and the development of the distal as well the proximal connecting fibers. Six principal stages were recognized: a) parallel, non-axonemal, developing basal bodies connected by a non-striated, proximal fiber, b) non-parallel, non-axonemal, mature basal bodies connected by a developing, striated, distal fiber; c) non-parallel, axonemal basal bodies connected by a fully developed, striated, distal fiber; d) opposite, axonemal basal bodies not connected by fibers, e) axonemal basal bodies not connected by fibers and directed backwards and f) parallel, axonemal basal bodies not connected by fibers. A headpiece, a 3-membered root and a reduced multilayered structure developed during ontogeny. The initial parallel disposition of the basal bodies, the initial lack of MLS and the presence of only two microtubular roots from the very inception of the basal apparatus development, suggest a Mamiella-like ancestor for Charales. Ontogenetic evidence supports previous ideas in the sense that similarities of sperm morphology of charalean and bryophytan gametes are likely due to convergent evolution. In addition, the present study clearly reveals the presence of centrin in Charales. Fil: Vouilloud, Amelia Alejandra Beatriz. Universidad Nacional del Sur. Departamento de Biología, Bioquímica y Farmacia. Laboratorio de Ficología y Micología; Argentina Fil: Caceres, Eduardo Jorge. Universidad Nacional del Sur. Departamento de Biología, Bioquímica y Farmacia. Laboratorio de Ficología y Micología; Argentina Fil: Leonardi, Patricia Ines. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca; Argentina. Universidad Nacional del Sur. Departamento de Biología, Bioquímica y Farmacia. Laboratorio de ...